Nghiên cứu chế tạo nhanh PAC bằng con đ−ờng axit và ứng dụng keo tụ nước thải tại một số xí nghiệp giấy tái chế xã Phong Khê (Bắc Ninh) - Khánh, Hồ Văn (Vietnam Journal of Chemistry, 2014)
In this paper, some results of study on fast preparation on polyalluminum chloride in acidic medium (PAC-a), characteristics and its ability in coagulation some of surfacewater were discussed. Experimental results shown that PAC-a has some advantages over the neutrally generated PAC: the production proceduce is more simple, it takes less time. Moreover, the consumption of PAC-a in coagulation of turbility of Red River and some wastewaters from production of reused paper is reduced